Factores de riesgo relacionados con la ruptura prematura de membrana en pacientes hospitalizadas en el Hospital General IESS de Babahoyo en el periodo de Enero 2024 a Junio del 2024. - Dávila Rocafuerte, Fernando Josué (2024)
Premature rupture of membranes (PROM) is a significant obstetric complication that increases the risk of preterm birth and other maternal-fetal complications; Therefore, the general objective of this research is to determine the risk factors related to PROM in patients hospitalized at the IESS General Hospital of Babahoyo during the period from January to June 2024, through the review of medical records and an approach comprehensive in the area of nursing. A quantitative methodology was used, based on the analysis of medical records of patients affected by PROM, complemented with interviews with health professionals and the results were that 69% of patients revealed that biological, infectious, obstetric and gynecological factors are significantly associated with PROM, in which several complications derived from this condition were identified, both for the mother and the fetus. Conclusions highlight the need for structured, evidence-based nursing interventions to mitigate risks and improve maternal-fetal health outcomes; Likewise, the implementation of continued training programs for nursing staff is suggested as a key preventive measure.